Utility of propidium monoazide viability assay as a biomarker for a tuberculosis disease. Issue 2 (March 2015) - Nikolayevskyy, Vladyslav; Miotto, Paolo; Pimkina, Edita; Balabanova, Yanina; Kontsevaya, Irina; Ignatyeva, Olga; Ambrosi, Alessandro; Skenders, Girts; Ambrozaitis, Arvydas; Kovalyov, Alexander; Sadykhova, Anna; Simak, Tatiana; et al.
Summary Reliable laboratory diagnosis of tuberculosis (TB), including laboratory biomarkers of cure, remains a challenge. In our study we evaluated the performance of a Propidium Monoazide (PMA) assay for the detection of viable TB bacilli in sputum specimens during anti-TB chemotherapy and its potential use as a TB biomarker. The study was conducted at three centres on 1937 sputum specimens from 310 adult bacteriologically confirmed pulmonary TB patients obtained before commencing anti-TB treatment and at regular intervals afterwards. Performance of the PMA assay was assessed using various readout assays with bacteriology culture results and time to positivity on liquid media used as reference standards. Treatment of sputum with N-acetyl-cysteine was found to be fully compatible with the PMA assay. Good sensitivity and specificity (97.5% and 70.7–80.0%) for detection of live TB bacilli was achieved using the Xpert® MTB/RIF test as a readout assay. Tentative Ct and ΔCt thresholds for the Xpert® MTB/RIF system were proposed. Good correlation (r = 0.61) between Ct values and time to positivity of TB cultures on liquid media was demonstrated. The PMA method has potential in monitoring bacterial load in sputum specimens and so may have a role as a biomarker of cure in TB treatment.